2011
DOI: 10.1097/pas.0b013e31820598a2
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Number or Complete Loss of Myoepithelial Cells Associated With Metaplastic and Neoplastic Apocrine Lesions of the Breast

Abstract: The presence of myoepithelial (ME) cells is considered an important feature in the vast majority of benign breast lesions. Recently, a case showing the absence of myoepithelium in a mammary duct with apocrine metaplasia was reported. To investigate the status of ME cells associated with apocrine metaplasia, the distribution of ME cells in 59 metaplastic and intraductal proliferative apocrine lesions was evaluated using immunohistochemical expression of p63 and Calponin. p63 showed a diminished number of ME cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 0 publications
4
66
0
Order By: Relevance
“…Although a lack of myoepithelial markers is commonly used as a hallmark for papillary carcinoma, it has reported that apocrine lesions, either benign or malignant, can show reduction and occasional complete loss of myoepithelial cells [1,8]. Tramm et al [8] described that a malignant diagnosis with apocrine changes of the breast cannot yet solely rely on the presence or absence of myoepithelial cells, and should be based on the overall morphology, i.e., the cytologic and architectural features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a lack of myoepithelial markers is commonly used as a hallmark for papillary carcinoma, it has reported that apocrine lesions, either benign or malignant, can show reduction and occasional complete loss of myoepithelial cells [1,8]. Tramm et al [8] described that a malignant diagnosis with apocrine changes of the breast cannot yet solely rely on the presence or absence of myoepithelial cells, and should be based on the overall morphology, i.e., the cytologic and architectural features.…”
Section: Discussionmentioning
confidence: 99%
“…Tramm et al [8] described that a malignant diagnosis with apocrine changes of the breast cannot yet solely rely on the presence or absence of myoepithelial cells, and should be based on the overall morphology, i.e., the cytologic and architectural features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytologic features of apocrine cells can be worrisome and, if associated with a reduction or loss in the myoepithelial cell layer, may prompt an erroneous diagnosis of malignancy. 3 Data regarding the relationship between apocrine metaplasia and invasive breast cancer are controversial; some authors have found an increase risk when associated with proliferative lesions, whereas others have found no such association. 5,6 It has been hypothesized that the same stimuli that cause breast cancer could also cause apocrine metaplasia.…”
Section: Commentmentioning
confidence: 99%
“…1 The loss of myoepithelial cells around benign and neoplastic apocrine lesions is well documented (Figure 2). 3 Apocrine cells can be found in several different histologic lesions and are often regarded as apocrine change. Among benign lesions with apocrine cells are apocrine metaplasia, apocrine adenosis, papillomas, fibroadenomas, and apocrine adenoma.…”
Section: Commentmentioning
confidence: 99%